Analisis Pesan Dakwah Pada Akun @Denaahaura Di Media Sosial Instagram - Reva Alryn Ferdhina; Muhammad Nasor; Ade Nur Istiani (STAI Bumi Silampari, 2026)
The development of communication technology has driven the transformation of da'wah delivery methods from conventional spaces to digital platforms that are more adaptive and closer to the younger generation. This study aims to analyze the content of da'wah messages conveyed through the Instagram account @denaahaura as a form of digital da'wah in the social media era. This study uses a content analysis method with a descriptive qualitative approach based on Klaus Krippendorff's theory. Research data were obtained through documentation techniques on @denaahaura's Instagram content in the form of feed uploads, video reels, captions, and audience interactions during the period November 2025 to February 2026. Sample selection was carried out using a purposive sampling technique and analyzed through the stages of unitizing, sampling, recording/coding, reducing, inferring, and narrating. The results of the study show that da'wah messages on the @denaahaura account can be classified into three main categories, namely faith, sharia, and morals. Of the three categories, moral messages are the most dominant form of messages and are packaged through a reflective, persuasive, and emotional approach. Furthermore, the strategy of conveying messages through aesthetic visuals, the use of light language, video reels, and a personal approach significantly increased audience engagement. Research findings indicate that Muslim female influencers serve not only as content creators but also as preaching communicators capable of building a digital spiritual space that is relevant, inspiring, and aligned with the characteristics of Generation Z and millennials.